PENGARUH EDUKASI BERBASIS LEMBAR BALIK TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN - Ariescha, Putri Ayu Yessy; Ariani, Peny; Purba, Silvia Kartika (Jurnal Inovasi Kesehatan Masyarakat, 2025)
The maternal mortality rate (MMR) remains a significant public health concern in Indonesia and serves as a key indicator in achieving the targets of the Sustainable Development Goals (SDGs). One of the major contributing factors to the high MMR is the delay in recognizing and managing pregnancy danger signs, which is often due to a lack of knowledge among pregnant women. Additionally, the suboptimal coverage of antenatal care (ANC) visits exacerbates this issue, as fewer women receive critical information during pregnancy. Providing education to pregnant women is a strategic effort to enhance their understanding and foster positive attitudes throughout pregnancy. One educational medium that can be utilized is the flipchart an interactive, visual, and communicative tool designed to deliver health information in an engaging and easy-to-understand manner. This study aimed to analyze the effect of flipchart-based education on improving pregnant women’s knowledge of pregnancy danger signs. A quasi-experimental design with a one-group pre-test–post-test approach was employed. The sample consisted of 17 primigravida women receiving antenatal care at Juliana Dalimunthe Clinic, selected through purposive sampling. A validated and reliable knowledge questionnaire was administered before and after the educational intervention. Data were analyzed using a paired sample t-test. The results showed a significant increase in knowledge among pregnant women regarding danger signs of pregnancy following the educational intervention, with a significance value of p = 0.004. These findings indicate that flipchart media is an effective educational tool in maternal health promotion. Not only does it improve maternal understanding of danger signs, but it is also expected to enhance awareness and motivation to attend regular ANC visits. Therefore, it is recommended that healthcare providers optimize the use of flipcharts in health education and counseling sessions for pregnant women, as part of preventive efforts to reduce complications.